Analysis of the Influence of Mood and Emotions on Legal Compliance Levels in Society - Khasanah, Dian Ratu Ayu Uswatun; Pongantung, Ronald Jolly (Magister Hukum Universitas Semarang, 2024)
This research aims to dig deeper into the relationship between mood, emotions, and societal legal compliance. The urgency of research lies in understanding the role of individual moods and emotions in legal compliance in society. Stability, security, and justice in society depend primarily on the level of compliance with the law, and this research highlights that an individual's mood and emotions can be a crucial factor in such compliance behavior. The focus of this research lies in the approach taken in analyzing the relationship between mood, emotions, and legal compliance, in contrast to previous research, which focused more on external factors such as law enforcement or socio-economic characteristics. This research approach method is sociological juridical and focuses on qualitative data. This research provides new insights into how these psychological factors influence legal compliance behavior in society. The finding is that positive moods, such as happiness and peace, promote higher legal compliance, while negative moods, such as anxiety or anger, can reduce legal compliance. The conclusions of this research emphasize the importance of considering psychological aspects in designing effective law enforcement policies and strategies. Understanding how mood and emotions influence legal compliance behavior can improve legal compliance and create a safer and more stable environment.